AN EVALUATION OF ENGLISH COURSEBOOKS FOR YOUNG LEARNERS - Veronica Listiani Diptoadi; Ruruh Mindari (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
Evaluating two English coursebooks used at Wima Kids English course, this study aims at finding out whether Hip Hip Hooray and Backpack fulfill the objectives of teaching English at Wima Kids and whether they are designed according to the principles of TEYL. Furthermore, in what aspects Hip Hip Hooray could be complemented with the materials in Backpack. The instruments used in this study were the researchers themselves equipped with an Evaluation Checklist by Bilash (2009) and in-depth interviews with some teachers who have used those two books in their classes. Using the check list, it was found out that Hip Hip Hooray and Backpack are in accordance with the objective of teaching English at Wima Kids, which is to help learners to be able to use English for communication, especially orally. The two series also fulfill the principles of TEYL. Further, the last finding revealed that Backpack can supplement Hip Hip Hooray series in language content, topic content, teaching tips and techniques, and grammar activities.